(untitled) (International Journal of Engineering and Computer Science, 2017)
In digital communication for transmission of very high data in secure and efficient way is the new approach for wireless communication system. So many techniques are developed to transmit the data in secure as well as in small space but all techniques are having some drawbacks. Large data encryption in small space and data privacy is two drawbacks leads to manipulations in handheld mobile transmissions. For transmission purpose we used image processing as well as communication concepts . In this paper we used DWT for barcode modulation in handheld devices to transmit the very high data through DPSKOFDM. Using DWT in barcode modulation for data transfer we are getting high accuracy and low complexity which can be shown by SNR vs. BER performance.